The structural phase transition in a hybrid layered perovskite: [C7H16N]2[SnI4]. (17th June 2017) - Li, Xue-Nan; Li, Peng-Fei; Wang, Zhong-Xia; Shi, Ping-Ping; Tang, Yuan-Yuan; Ye, Heng-Yun
Graphical abstract: Compound1 undergoes a reversible structural phase transition from the high-temperature space group Cmca to the low-temperature space group P 21 / c at around T c  = 319 K. The driving force of the phase transition is ascribed to the order–disorder transformation of the organic cations. Abstract: We investigated the synthesis and structural phase transition of a two-dimensional layered perovskite-type organic–inorganic hybrid compound, (cyclohexylmethylammonium)2 SnI4 . By systematic characterizations, we found that this compound undergoes a reversible first-order phase transition from the high-temperature space group Cmca to the low-temperature space group P 21 / c at around T c  = 319 K. Accompanying the phase transition, dielectric bistability was also detected. The phase transition is ascribed to the order–disorder transition of the cyclohexylmethylammonium cations. It is known, the interesting electronic and optical properties in the two-dimensional Sn(II) and Pb(II) halide perovskite structures are dominated by the inorganic part. The phase transition and related physical properties observed in this work arise from the organic parts. This will enrich the chemistry of the hybrid structures by tailoring the organic moieties, and accordingly, may lead to novel multifunctional materials such as ferroelectric materials.